Clareamento interno em dentes despolpados como alternativa a procedimentos invasivos: relato de caso - Bortolatto, Janaina [UNESP]; Corsi, Christian Eduardo [UNESP]; Presoto, Cristina Dupim [UNESP]; Cioffi, Sabrina Spinelli [UNESP]; Oliveira Júnior, Osmir Batista de [UNESP] (My University, 2012)
The increasing interest of patients for a better aesthetic appearance of their smile, associated with the development of new materials and techniques, encouraged by media couverage of this concept of beauty, provided an important evolution of cosmetic dentistry. As the darkness of a single anterior tooth or a group of teeth, in most cases, impairs the appearance of the smile and there is growing appreciation of the less invasive procedures, the technique of tooth bleaching is an important option for aesthetic treatment. To have success in the bleaching treatment, it is important to have knowledge of the origin, nature and composition of the stain. Among the causes of color changes acquired post-eruptive, dental trauma, with or without pulp necrosis, is one of the most commonly encountered etiologies, characterized by a reddish-brown color. Current techniques of bleaching for teeth treated endodontically employ oxidative agent hydrogen peroxide. The objective of this paper is to describe the immediate technique of bleaching non-vital tooth by presenting a clinical case.

O crescente interesse dos pacientes por uma melhor aparência estética do sorriso, associado ao desenvolvimento de novos materiais e técnicas, incentivados por uma divulgação na mídia desse conceito de beleza, propiciou uma evolução importante da odontologia estética. Como o escurecimento de um único dente anterior ou de um grupo de dentes, na maioria das vezes, interfere negativamente na aparência do sorriso e há cada vez mais uma valorização dos procedimentos menos invasivos, a técnica de clareamento dental representa uma opção importante de tratamento estético. Para que se tenha sucesso no tratamento clareador, é importante ter o conhecimento da origem, da natureza e da composição da mancha. Entre as causas das alterações de cor adquiridas pós-eruptivas, o traumatismo dental, associado ou não à necrose pulpar, é uma das etiologias mais comumente encontradas, caracterizando-se por uma coloração marrom-avermelhada. As atuais técnicas de clareamento para dentes tratados endodonticamente empregam como agente oxidativo o peróxido de hidrogênio. O objetivo deste artigo é descrever a técnica imediata de clareamento de dente não vital por meio da apresentação de um caso clínico.
Internal bleaching of pulpless teeth as an alternative to invasive procedures: case report
Keywords: Tooth Bleaching; Hydrogen Peroxide; Esthetics; Clareamento dental; Peróxido de Hidrogênio; Estética